Adverbial Adjunct Clause Found in The Novel “The Happy Prince and Other Tales”: A Syntax Analysis - Ni Komang Ratna Shinta Dewi (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2024)
In the novel "The Happy Prince and Other Tales" by Oscar Wilde, published in 1888, adverbial adjunct clauses are frequently used to qualify the main clause process concerning agencies such as time, means, causes, and ends, often with elements that determine the nature of their relationship (Langacker 2008: 419–420). There are 93 sentences using adverbial adjuncts of different types, including time, place, reason or cause, manner, degree, and frequency. The novel is colorful with the use of these subordinate clauses. This analysis focuses on the use of adverbial adjunct clauses in the novel to convey the philosophical and idealistic meaning of human life and society. "The Happy Prince and Other Tales" is interesting to analyze because the language is very easy to understand and consists of no more than one hundred pages.